Islam and Women’s Involvement in Education (Abu Syuqqah Thought Study in Taḥrīr al-Mar’ah Fī ‘Aṣr al-Risālah) - Juhri Jaelani; Syahidin Syahidin; Elan Sumarna (Perhimpunan Intelektual Muslim Indonesia, 2021)
Islam has a view to put things in everything in a balanced position (tawazun). Islam also places men and women as human beings with the same position. However, there are still many who differentiate the position of men and women as creatures of God. One of these differences can be seen from the minimal contribution of a woman or Muslim woman in the field of education. In fact, education is very important because women are the future mothers of their children. After all, education starts from within the family and that is where the role of women as mothers is very significant. This study aims to reveal Abu Syuqqah's thoughts on Islamic acknowledgment of women's involvement in the field of education, which he produced through an effort to reinterpret religious authoritative texts related to women's activities during the prophetic period. This research is also expected to provide understanding and motivation about the balance of roles and contributions of men and women. This study uses a qualitative approach with library research methods. The data collection technique in this study was based on the main source of the book by Abu Syuqqah entitled Taḥrīr al-Mar'ah Fī 'Aṣr al-Risālah, supported by religious authoritative books and scientific journals relevant to the research theme. The results of the study indicate that the call of Islam regarding the obligation to seek knowledge to its adherents is universal, so that there is no legal distinction for both Muslims and Muslim women. Islam also holds that women have the right to get proper education and good teaching as Muslims get. Based on this, according to Abu Syuqqah, the status of women is not an obstacle for Muslim women to have a high spirit in seeking and developing knowledge. The form of women's involvement in education can be in the form of women as students who receive knowledge, or as female teachers who convey knowledge.